Interactive directional ambient occlusion and shadow computations for volume ray casting - Campagnolo, Leonardo Quatrin; Celes, Waldemar (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
Volume rendering is a widely used technique to visualize 3D scalar data. To enhance visual shape and depth perception, distinct illumination techniques have been proposed, adding different types of lighting effects. In this paper, we explore a new strategy to compute directional ambient occlusion and shadows for volume ray casting to render structured datasets. Our algorithm computes occlusion of traced cones by evaluating Gaussian integrals at discrete samples along the cone axis. The computed occlusion is then used to add directional ambient occlusion effects and to generate shadows. Given the extinction coefficient data volume, we create one extra volume computing representative amplitudes of Gaussian functions. Mipmapping is then used to effectively evaluate Gaussian integrals with different sizes placed along the cone axis, adapting a circle packing approach. We demonstrate that the proposed method delivers a better balance between quality results and performance when compared to previous specialized procedures, with the advantage of combining directional ambient occlusion and shadow generation under the same framework.